Race, Neoliberalism, and “Welfare Reform” in Britain - Fisher, Tracy (Social justice, 2006)
Part of a special issue on resistance to neoliberal globalization. The writer employs an intersectional approach to examine the effects of the rise of neoliberalism on a sample of poor and working-class women of color in Great Britain and discusses the role of the government-funded, community-based Southwark Black Women's Centre (SBWC) in easing their hardships. She suggests that neoliberalization is neither uniform nor unilinear and that its effect is unequal and differential among specific classes, races, and genders. Moreover, the writer contends that neoliberalization bolsters racial hierarchies and redefines the terms of citizenship to leave poor and low-income women of color and their families on the margins of society.